A method of using Si L-edge for O/Si and N/Si quantitative ratio analysis by electron energy loss spectroscopy (EELS). (July 2021) - Wang, Yun-Yu; Chan, Sook Fun; Jin, Qiang; Zhuang, Kent; Choi, Jae Kyu
Highlights: The paper describes a method to remove thickness dependent effect on O/Si and N/Si by electron energy loss spectroscopy. This analysis is critical for tunnel oxide of non-volatile memory 3D NAND structure. A linear relationship between inverse jump ratio of Si L-edge and O/Si and N/Si intensity ratio is found for electron energy loss spectroscopy (EELS) analysis. This relationship is used to analyze O/Si and N/Si atomic ratio to quantify the elemental distribution in SiON films and the result is compared with XPS analysis on the same SiON films. The method is applied to blanket wafer elemental analysis and can be used for flash memory structure to obtain atomic ratios of N/Si and O/Si for tunnel oxide at sub-nanometer scale independent of sample thickness. Abstract: In EELS core loss excitation, inverse jump ratio is defined as a ratio between intensity of a pre-core-loss-edge and a signal of the core loss excitation after background subtraction. A linear relationship between inverse jump ratio of Si L-edge and O/Si and N/Si intensity ratio is found for electron energy loss spectroscopy (EELS) analysis. This relationship is used to analyze O/Si and N/Si atomic ratio to quantify the elemental distribution in SiON films and the result is compared with XPS analysis on the same SiON films. The method is applied to blanket wafer elemental analysis and can be used for flash memory structure (3D NAND) to obtain atomic ratios of N/Si and O/Si for tunnel oxide at sub-nanometer scale.